Taro [Colocasia esculenta (L.) Schott]: a critical review of its nutritional value and potential for food application - BRANDÃO, Natali Alcântara; TAGLIAPIETRA, Bruna Lago; CLERICI, Maria Teresa Pedrosa Silva (Food Science and Technology, 2023)
Taro [Colocasia esculenta (L.) Schott] is an important food source worldwide, as it contains several macro- and micronutrients, standing out as a source of polysaccharides such as starch, mucilage, minerals, and bioactive compounds, including flavonoids. However, taro also contains antinutrients, such as oxalates, which impede its consumption in the fresh form. This critical review addresses the main studies on the physicochemical and nutritional composition of the tuber in fresh, cooked, or flour form, in addition to various food applications, aiming to improve the scientific and industrial visibility of this tuber.